Letter from Edmund G. Brown Jr - Edmund G. Brown Jr.:::::: (1991)
This January 14, 1991 letter from California Democratic Party Chair Edmund G. Brown Jr. congratulates recipients on their selection to the 1991–92 California Democratic State Central Committee and encourages attendance at the upcoming State Convention. He outlines key convention business, including electing party officers and adopting 1991 resolutions, and notes that prospective presidential and U.S. Senate candidates are expected to attend. The letter accompanies a registration packet with agenda, proxy, hotel, transportation, and rules information.